The role of risk, religiosity, fairness, and norms on attitude and intention of movie piracy: insight from the perspective of young Indonesian users - Massijaya, Muhammad Azwar; Mohamed, Rosmah; Bali Mahomed, Anuar Shah (Cogent OA, 2025)
This article fills a theoretical gap in the literature by incorporating perceived risk theory, equity theory, religiosity theory, social norm theory, and the theory of planned behavior to investigate key factors influencing the movie piracy attitude and intention. This research was conducted using convenience sampling of 327 respondents in Jabodetabek. Data were analyzed using PLS-SEM. Risk, fairness, and intrinsic religiosity have a significant influence on attitude and intention toward movie piracy, while extrinsic religiosity and descriptive norms do not. This research also confirmed the significance of attitude toward the intention of movie piracy. Governments and movie producers should launch communicative social advertisements to emphasize the risk involved when watching pirated movies. The effort needed to produce a movie also should be highlighted. In addition, religious leaders may support the government and movie industry by informing people through religiosity aspect.